Tumors located in the central column of the liver are associated with increased surgical difficulty and postoperative complications following open liver resection for colorectal metastases. Issue 8 (August 2022) - Azoulay, Daniel; Desterke, Christophe; Bhangui, Prashant; Salloum, Chady; Conticchio, Maria; Vibert, Eric; Cherqui, Daniel; Adam, René; Ichai, Philippe; Saliba, Faouzi; Elmaleh, Annie; Naili, Salima; et al.
Abstract: Background: To assess the impact of difficult location (based on preoperative computed tomography) of liver metastases from colorectal cancer (LMCRC) on surgical difficulty, and occurrence of severe postoperative complications (POCs). Methods: A retrospective single-centre study of 911 consecutive patients with LMCRC who underwent hepatectomy by the open approach between 1998 and 2011, before implementation of laparoscopic surgery to obviate approach selection bias. LMCRC with at least one of the following four features on preoperative imaging: tumor invading the hepatocaval confluence or retro-hepatic inferior vena cava, centrally located (Segments 4, 5, 8) and >10 cm in diameter, abutting the supra-hilar area, or involving the paracaval portion or caudate process of Segment 1; were considered as topographically difficult (top-diff). Independent predictors of surgical difficulty assessed by number of blood units transfused, duration of ischemia, and number of sessions of pedicle clamping during surgery and of severe POCs were identified by multivariate analysis before, and after propensity score matching. Results: Top-diff tumor location independently predicted surgical difficulty. Severe POCs were associated with the tumor location [top-diff vs. topographically non difficult (non top-diff)], preoperative portal vein embolization, and variables related to surgical difficulty. Conclusion: LMCRC in difficult location independently predicts surgical difficulty and severe POCs.